19 THE EFFECT OF DIETARY PHOSPHORUS ON VASCULAR CALCIFICATION AND OSTEOPONTIN EXPRESSION IN NORMAL AND UREMIC ANIMALS. (1st March 2005) - Aly, Z. Al; de Graaf, W.; Kowalewski, R. A.; Salinas-Madrigal, L.; Martin, K. J.; González, E. A.
Abstract : Vascular calcification is a very common finding in patients with chronic kidney disease. It is an independent strong predictor of cardiovascular morbidity and mortality. Hyperphosphatemia is also common in patients with chronic kidney disease and elevated phosphate levels also are associated with increased cardiovascular mortality. It has been hypothesized that derangements in divalent mineral metabolism play a role in vascular calcification. It has been recently shown that elevated phosphorus levels induce calcification of human smooth muscle cells in vitro. Phosphate has been shown to be a specific signal for induction of osteopontin (OPN) gene expression. We wished to examine the effect of dietary phosphorus on ectopic vascular calcification and OPN gene expression in normal and uremic rats. Renal failure was induced in 12-week-old Wistar rats by feeding them a diet containing 0.75% adenine for 4 weeks. Normal and uremic animals were fed either a high or a low phosphorus diet for 8 weeks. Serum chemistries were obtained at week 4 and at time of sacrifice. Heart and aorta were histopathologically analyzed for the presence or absence of calcification. Aortas were examined for the expression of OPN mRNA. We found hyperphosphatemia, a lower body weight and increased mortality in the uremic group fed a high phosphorus diet. Calcification was present in the cardiovascular tissue (heart and aorta) and OPN mRNA levels were increased in aortic tissue isolated from uremic rats fed a high phosphorus diet. There was no cardiovascular calcification seen in the other groups. Interestingly, OPN mRNA was increased in aortic tissue isolated from nonuremic rats fed a high phosphorus diet. Our findings demonstrate that increased dietary phosphorus is associated with cardiovascular calcification in uremic animals. Furthermore, the results indicate that high phosphorus diet even in the absence of hyperphosphatemia or uremia is associated with increased expression of OPN mRNA. The findings suggest that increased dietary phosphorus may induce the synthesis of bone matrix proteins in cardiovascular tissue. This may then facilitate the process of vascular calcification in the presence of factors such as increased calcium × phosphorus product and other factors that are related to the uremic milieu.